2005
DOI: 10.1097/01.mlg.0000161358.20450.12
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Endoscopic Evaluation of Swallowing With Sensory Testing in Patients With Unilateral Vocal Fold Immobility: Incidence and Pathophysiology of Aspiration

Abstract: Dysphagia in patients with unilateral vocal fold immobility is demonstrated during FEESST by pooling, spillage, penetration, and aspiration. The pathophysiology of dysphagia is multifactorial with decreased sensation and limitation of airway protective mechanisms both acting as contributing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 10 publications
3
82
0
2
Order By: Relevance
“…Previous studies have reported that nearly 56% of patients with VCP have swallowing dysfunction [4, 5]. Tabaee et al [6] suggested that dysphagia in patients with VCP has multifactorial causes, including limited airway protection and decreased laryngopharyngeal sensation based on the findings of flexible endoscopy. Heitmiller et al [7] asserted that aspiration resulted from impaired airway protection rather than esophageal obstruction in patients with unilateral vocal fold motion impairment, and recommended video pharyngoesophagography as the technique of choice to identify patients at risk for aspiration.…”
mentioning
confidence: 99%
“…Previous studies have reported that nearly 56% of patients with VCP have swallowing dysfunction [4, 5]. Tabaee et al [6] suggested that dysphagia in patients with VCP has multifactorial causes, including limited airway protection and decreased laryngopharyngeal sensation based on the findings of flexible endoscopy. Heitmiller et al [7] asserted that aspiration resulted from impaired airway protection rather than esophageal obstruction in patients with unilateral vocal fold motion impairment, and recommended video pharyngoesophagography as the technique of choice to identify patients at risk for aspiration.…”
mentioning
confidence: 99%
“…However, this has been little studied in the clinical literature. Both work on breathing [37] and dysphagia [38,39] are inconclusive with regard to the effect of resting position of the paralyzed vocal fold on impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of aspiration among patients with UVFI is 18-38 % [ [47][48][49]. Therefore, if a patient complains of dysphagia, or aspiration is suspected, further evaluation of their swallowing function should be performed.…”
Section: Formal Evaluation Of Swallowingmentioning
confidence: 99%